ENGINEERING AND SAFETY ACTIONS OF A VETERINARY VIRAL VACCINE LABORATORY - A CASE STUDY - PRATES, Glaucia Aparecida; NASCIMENTO, Maria Cristina Pacheco do; GOVEIA, Danielle; CAMPOS, Cristiane Inácio de; GAVA, Maristela (Revista Brasileira de Engenharia de Biossistemas, 2013)
This study aims to evaluate the control measures in a veterinary viral vaccine laboratory located in Curitiba, Paraná- Brazil . It was made by a evaluation on the personal protective equipment ( PPE ) and Collective Protective equipment ( CPE ) through analysis of Program Environmental Risk Prevention - PPRA and identify the compliance of biological, chemical and physical hazards according to the regulations 6 ( NR 6 ) and 9 (NR 9). Comparing with the Information Sheet for Chemical Safety - MSDS , it was observed that there were gaps in the sectors evaluated with respect to respiratory protective PPE 9 % . In the PPRA was found that 183 PPE were recorded , missing the inclusion of PPE in 16 different chemicals . Since this lack of 9%. It turned out in detail the non-inclusion of PPE in the percentage of 7 % , 10 % , 12 % , 6 % , 17 % , 2 % , 27 % and 8 % respectively of the first sector to sector 8. Considering the results and analysis , could -If conclude that the above objectives analyzed were achieved despite the limitations of data collection due to constraint correct input on the premises by the standards of biosecurity.